1 3 3

:

  1. #1

    Jul 2012
    5,302

    :-
    :-
    1- ^3 - ^2 - ^2 -
    :-
    = ( ^3 - ^2 ) - ( ^2 - )
    = ^2 ( - ) - ( - )
    = ( - ) ( ^2 - )
    = ( - ) ( - 1 )

    2- ^3 - - ^2 + 1
    :-
    = ( ^3 - ^2 ) - ( - 1 )
    = ^2 ( - 1 ) - ( - 1 )
    = ( - 1 ) ( ^2 - 1 )
    = ( - 1 ) ( - 1 ) ( + 1 )

    3- ^2 + 9 ^2 - ^2 - 6
    :-
    = ( ^2 - 6 + 9 ^2 ) - ^2
    = ( - 3 )^2 - ^2
    = [ ( - 3 ) - ] [ ( - 3 ) + ]
    = ( - 3 - ) ( - 3 + )

    :-

    4 + 14 - 2 ^2 - 7
    :-
    = 2 ( 2 + 7 ) - ( 2 + 7 )
    = ( 2 + 7 ) ( 2 - )
    :
    4 + 14 - 2 ^2 - 7 = ( 4 - 2 ^2 ) + ( 14 - 7 )
    = 2 ( 2 ( 2 - ) + 7 ( 2 - )
    = ( 2 - ) ( 2 + 7 )

    :-
    :-
    1- 4 ^2 - 4 + -
    :-
    4 ^2 - 4 ) + ( - )
    4 ( - ) + ( - )
    ( - ) ( 4 + )
    *************
    2- 20 - 4 - 15 + 3
    :-
    ( 20 - 4 ) - ( 15 - 3 )
    4 ( 5 - ) - 3 ( 5 - )
    ( 5 - ) ( 4 - 3 )

    :-
    4 ^2 - 4 ^2 + 12 - 9
    :-
    4 ^2 - ( 4 ^2 - 12 + 9 )

    4 ^2 - ( 2 - 3 )^2

    ( 2 - ( 2 - 3 ) ) ( 2 + ( 2 - 3 )
    ( 2 - 2 + 3 ) ( 2 + 2 - 3 )

    :-

    ^2 + ^2 - ^2 - ^2
    :- \
    = ( ^2 - ^2 ) + ( ^2 - ^2 )
    = ^2 ( - ) + ^2 ( - )
    = ^2 ( - ) - ^2 ( - )
    = ( - ) ( ^2 - ^2 )
    ( - ) ( - ) ( + )











  2. #2

    Jul 2012
    5,302

    :

    :-

    3 ^2 - 3 ^2 - 6 ^2 + 6 ^2
    :-
    3 ^2 ( - ) - 6 ^2 ( - )
    3 ^2 ( - ) + 6 ^2 ( - )
    ( - ) ( 3 ^2 + 6 ^2 )
    ( - ) 3 ( + 2 )
    3 ( - ) ( + 2 )

    :-
    :
    ^2 + 4 + 4 ^2 - 25 ^2
    :-
    ^2 + 4 + 4 ^2 - 25 ^2
    = ( ^2 + 4 + 4 ^2 ) - 25 ^2

    = ( + 2 )^2 - 25 ^2


    = ( ( + 2 ) - 5 ) ( ( + 2 ) + 5 )

    = ( + 2 - 5 ) ( + 2 + 5 )

    :-
    :
    1- 3 + 12 + + 4
    :-

    ( 3 + 12 ) + ( + 4 )
    3 ( + 4 ) + ( + 4 )
    ( + 4 ) ( 3 + 1 )







  3. #3
      Eiman
    Jul 2011
    -
    14,750

    :

    .......

: 1 (0 1 )